Disseminated superficial actinic porokeratosis in an elderly patient undergoing androgen deprivation therapy for advanced prostate cancer: exploring the potential association - Paulus Anthony Halim; Shannaz Nadia Yusharyahya; Lili Legiawati; Rinadewi Astriningrum; Sondang P. Sirait (PAGEPress Publications, 2024)
Porokeratosis is a group of chronic dermatoses characterized by the presence of cornoid lamellae. Disseminated superficial actinic porokeratosis (DSAP) is a common subtype, presenting as multiple small annular scaly lesions primarily in sun-exposed areas. While previous studies have documented DSAP in prostate cancer patients, the association with androgen deprivation therapy (ADT) has not been reported. In this report, we describe an elderly patient with advanced prostate cancer, who developed DSAP subsequent to undergoing ADT. We present the clinical, dermoscopic, and histopathological evaluations, and discuss the potential role of ADT in the pathogenesis of DSAP.